EFEK PENAMBAHAN ATOM TEMBAGA (Cu) DAN PERAK (Ag) PADA MATERIAL AKTIF NANOMATERIAL ZnO SEL SURYA FOTOELEKTROKIMIA - Windayani Windayani; Iwantono Iwantono; Awitdrus Awitdrus; Zulkarnain Zulkarnain (Universitas Riau, 2019)
ZnO material coated with Cu + Ag was successfully grown using seed mediated hydrothermal method at a temperature of 90° C for 8 hours with a variation of concentration of Ag, 10 mM, and 20 mM. The growth of ZnO nanomaterials was carried out on the FTO substrate (Flourine Tin Oxide). The Samples were characterized using, Field Emission Scanning Microscope (FESEM), and X-ray Diffraction (XRD). The FESEM photos show ZnOnanorod coated with Cu + Ag have grown on FTO having a nanoflower shape that consructed from ZnOnanorods with their orientation . The XRD pattern shows five peaks at 2θ: 31.69 °; 34.36 °; 36,18 °; 47.52 °; and 56.4 °. Based on the results of the analysis of the OriginPro 8 program each peak in a row according to the crystal orientation (100), (002), (101), (012), and (110). The stongest line was found in the crystal plane (101). DSSC was fabricated using ZnO nanomaterial coated with Cu + Ag as active material, N719 dye, liquid electrolyte, and plastisol as catalyst on the counter electrode. The results of I-V measurements at halogen lamp with ilumination its intensity of 100 mW/cm2 of the cells has producedthe highest efficiency value based on Cu coated ZnO was based DSSC 0,98% with a Cu concentration of20mM.These results show that the addition of Cu layer can increase the efficiency of DSSC based on ZnO by 123% compared to ZnO without Cu based DSSC. Addition of Ag to active material of Cu coated ZnO nanomaterial did not have a positive effect on the efficiency of DSSC cells.